Asuhan Keperawatan Pada An. G Dengan Kejang Demam - Anggi, Anggi Olivia; Handayani, Reska; Sari, Putri Minas; Yanti, Erpita (Universitas Negeri Padang, 2025)
ABSTRACT Febrile seizures are seizures that occur when the temperature rises to 38°C caused by an extracranial process, usually occurring at the age of 3 months to 5 years. Febrile seizures begin with an increase in body temperature. An increase in body temperature that is not treated immediately will cause seizures. In West Sumatra, especially at Prof. H. Muhammad Yamin SH Regional Hospital. in 2022, the incidence of febrile seizures was 154 children who experienced febrile seizures. The purpose of this scientific paper is to provide nursing care to patients with febrile seizures in the children's room at Prof. H. Muhammad Yamin SH Regional Hospital. A case study approach is used with a nursing process that includes assessment, diagnosis, planning, implementation, and evaluation. Patient care was carried out on February 27 - March 3, 2025, which was carried out with assessment, data analysis, diagnosis, planning, implementation and evaluation. After the assessment was completed, 3 diagnoses were obtained, namely hyperthermia related to the disease process as evidenced by body temperature above normal values, warm skin and seizures, knowledge deficit related to lack of exposure to information as evidenced by as evidenced by asking about the problems faced, and the risk of nutritional deficit as evidenced by weakness and loss of appetite. After nursing care was obtained from An. G, the nursing problems were resolved. Appropriate and comprehensive nursing care plays a very important role in supporting the healing process of children with febrile seizures. This scientific paper also emphasizes the imprortance of families and parent to pay attention to the cleanliness of the home environment, when a child has a fever, thw mother must also compress her child’s body with warm water, the mother must also ensure that her cild drinks plenty of fluids so that the child does not become dehydrated, parents must also be aware of signs of fever such as routinely measuring the child’s body temperature when the child looks lethargic, fussy or hot.